Tindak Pidana Memperdagangkan Barang dan Jasa yang Tidak Sesuai dengan Standar yang Dipersyaratkan: Studi Kasus Putusan Nomor : 474/PID/SUS/2017/PN.Kwg. - Rikmadani, Rd. Yudi Anton; Simorangkir, Alexandro P; Deky Akhmad Maulana (Advokasi Hukum & Demokrasi (AHD), 2025)
This study aims to find out about the regulation of criminal acts in the field of trading goods that are not in accordance with standards (Case Study of Karawang District Court Decision Number: 474/Pid.Sus/2017/PN. Kwg). It is hoped that this research can explain the regulation of criminal acts and the consideration of judges in deciding criminal cases as stipulated in Law Number 8 of 1999 concerning Consumer Protection. This research is a normative legal research using a case approach. The legal materials used are secondary legal materials, primary legal materials, and tertiary legal materials. The results of the research are, first, criminal acts in the field of producing and/or trading goods that do not follow the conditions as stated in the goods label have violated Article 8 paragraph (1) letter e Jo Article 62 of the Consumer Protection Law with a minimum penalty of 5 years in prison. Second, the judge's consideration in imposing the verdict was based on complaints from consumers who were aggrieved by a prison sentence of 7 (seven) months. Based on the decision, it is hoped that it can create a sense of justice for the community.